CURCUMIN INDUCES ANOIKIS IN H460 NON-SMALL LUNG CANCER CELLS THROUGH SUPEROXIDE ANION INDUCTION - Pongrakhananon, V.; Luanpitpong, S.; Chanvorachote, P.; Nimmannit, U. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Anoikis or apoptosis triggered by loss of cell anchorage plays an important role in prevention of tumor cell metastasis. During metastasis process, anticancer drugs are not able to completely eliminate cancer cells that suspended in the blood stream; therefore, the use of natural safety compounds to enhance apoptosis of these suspended cells may improve the therapy. Curcumin (diferuloylmethane), a major active component in turmeric, Curcuma longa, has been shown to inhibit neoplastic initiation, promotion and progression of a wide variety of tumor cells. However, the effect of curcumin on anoikis process has not been well characterized. We herein demonstrated that 10 ÂµM of curcumin triggered 1.2-folds anoikis of detached lung carcinoma H460 cells compared with controlled cells. Cell viability was detected by XTT assay and anoikis cells were indicated by annexin V staning assay. Mechanism of curcumin induced anoikis was associated with its ability to generate intracellular reactive oxygen species (ROS). Curcumin caused 1.6-folds induction of intracellular ROS level as detected by DCF-DA and flow cytometry. Our inhibitory study revealed that superoxide anion generated by curcumin was a principle ROS responsible for anoikis induction in these cells. Thus, our results showed that curcumin induced anoikis in detached-H460 cells resulted from increasing of intracellular ROS.